The GO-Fe3O4 /Psf Membrane Prepared by Phase Inversion for Filtration: Dyes and NaCl in Water - Munasir Nasir; Yekti Purnama Utami; Nuhaa Faaizatunnisa; Lydia Rohmawati; Evie Suebah; Ahmad Taufiq; Ezza Syuhada Sazali (Journal of Water and Environmental Nanotechnology)
This study aims to determine the effectiveness of the GO- Fe3O4/Psf membrane in filtering water contaminated with dyes and salt. The membrane was prepared using the phase inversion method, with variations in the composition of GO- Fe3O4 (0.25%, 0.50%, 0.75%, and 1.00%), with polysulfone as the polymer material and NMP as a diluent. The dead-end filtration method is used to study the ability to repel dyes and salt molecules in water. Hydrophilicity (surface contact angle test) and morphology (SEM) to confirm the membrane profile. Furthermore, rejection and filtration performance tests were carried out on water contaminated with dye (methylene blue) and water containing salt through salt rejection, flow flux, and UV-VIS tests. The filtration test results showed that the membrane with a composition of 0.75% had a salt rejection percentage of 59.33% (the highest), and the lowest flow flux was 54.42 L.m-2.h-1. The dye filtering results (MB) showed better performance on the same membrane. It has been observed that the permeate is brighter than the other membranes. These results indicate that the membrane with a GO- Fe3O4 concentration of 0.75 wt.% is the most effective compared to other membranes in filtering water. The presence of Fe3O4 nanoparticles increases the efficiency and durability of graphene membranes in salt rejection by increasing the surface charge and selectively adsorbing salt ions.